2018
DOI: 10.1089/ten.tea.2017.0424
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Bone Marrow and Cord Blood Mesenchymal Stem Cells for Cartilage Self-Assembly

Abstract: Joint injury is a common cause of premature retirement for the human and equine athlete alike. Implantation of engineered cartilage offers the potential to increase the success rate of surgical intervention and hasten recovery times. Mesenchymal stem cells (MSCs) are a particularly attractive cell source for cartilage engineering. While bone marrow-derived MSCs (BM-MSCs) have been most extensively characterized for musculoskeletal tissue engineering, studies suggest that cord blood MSCs (CB-MSCs) may elicit a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…A stark difference in the chondrogenic potential of BMSCs and CBMSCs was observed in vitro, whereby significantly higher Alcian blue staining was observed in CBMSC compared to BMSC pellets. This has not been reported previously in the typical chondrogenic pellet tri-lineage protocols, however it is in line with recent observations that CBMSCs form cartilage in vitro that is more histologically and mechanically equivalent to native cartilage compared to that formed by BMSCs 29 and that unprimed CBMSCs formed significantly higher quantities of cartilage in vivo compared with BMSCs in a ceramic-based assay similar to the current study 30 . Together, these suggest that CBMSCs may be superior for cartilage regeneration applications compared with BMSCs, which warrants further investigation.…”
Section: Discussionsupporting
confidence: 93%
“…A stark difference in the chondrogenic potential of BMSCs and CBMSCs was observed in vitro, whereby significantly higher Alcian blue staining was observed in CBMSC compared to BMSC pellets. This has not been reported previously in the typical chondrogenic pellet tri-lineage protocols, however it is in line with recent observations that CBMSCs form cartilage in vitro that is more histologically and mechanically equivalent to native cartilage compared to that formed by BMSCs 29 and that unprimed CBMSCs formed significantly higher quantities of cartilage in vivo compared with BMSCs in a ceramic-based assay similar to the current study 30 . Together, these suggest that CBMSCs may be superior for cartilage regeneration applications compared with BMSCs, which warrants further investigation.…”
Section: Discussionsupporting
confidence: 93%
“…Further randomized controlled trials are definitely required to estimate the potential of MSCs in cartilage repair and to evaluate advantages and disadvantages of stem cell treatment. Several experiments done in animal models of knee OA have shown that MSC therapy may delay progressive degeneration of the joint [79, 80]. In a rabbit model, it was demonstrated that single intra-articular infusion of synovial MSCs into the knee leads to cellular adherence close to meniscal defect and supported meniscal regeneration [81].…”
Section: Potential Side Effects Of Exogenous Mscs After Their Admimentioning
confidence: 99%
“…Another study also shows the in vitro cultured ADMSCs can form colonies via rapid proliferation . 3) MSCs are considered to possess multidirectional differentiation capacity, including osteogenesis, chondrogenesis . The ADMSCs in collagen‐based hydrogel can undergo the differentiation into chondrocytes and form tissue engineered cartilage .…”
Section: Therapeutic Cells and Growth Factorsmentioning
confidence: 99%